2019
DOI: 10.9734/acri/2019/v19i130149
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Meteorological Parameters on Particle Pollution (PM2.5 and PM10) in the Tropical Climate of Port Harcourt, Nigeria

Abstract: Aims: This study explores the influence of meteorological parameters such as wind direction, wind speed, rainfall, air temperature and relative humidity on PM2.5 and PM10 concentration. Place and Duration of Study: The study was conducted in Woji, an urban area of Port Harcourt city in Nigeria, between May and December 2019 covering wet and dry season. Methodology: The PM10 and PM2.5 concentrations were monitored for 236 days using photometric laser based particulate monitor while meteorological pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The influences of the wind direction and speed, rainfall, ambient temperature and relative humidity on the PM 2.5 , and PM 10 concentration values were presented in a study at an urban site in Port Harcourt, West Africa [9]. It was reported that the wind speed, rainfall and ambient temperature all significantly affected the PM 2.5 , and PM 10 concentration values but with weak correlations.…”
Section: Introductionmentioning
confidence: 99%
“…The influences of the wind direction and speed, rainfall, ambient temperature and relative humidity on the PM 2.5 , and PM 10 concentration values were presented in a study at an urban site in Port Harcourt, West Africa [9]. It was reported that the wind speed, rainfall and ambient temperature all significantly affected the PM 2.5 , and PM 10 concentration values but with weak correlations.…”
Section: Introductionmentioning
confidence: 99%
“…Relative humidity (RH) showed negative correlation with SPM concentrations ( r = −0.16) indicating that moisture settles the suspended dust particles by wetting and preventing crustal soil particles re-suspension in the atmosphere (Kulshrestha et al , 2004; Khillare and Sarkar, 2012; Wang et al , 2019). Overall correlation between p.m. 2.5 and RH is 0.5 indicating not so significant relation between the two (Onuorah et al , 2019). Spatial and seasonal variations exist between p.m. 2.5 and RH (Yang et al , 2017), during summer there is no relationship observed between p.m. 2.5 and RH ( r = 0) and during winter insignificant relation is observed between p.m. 2.5 and RH ( r = 0.2).…”
Section: Resultsmentioning
confidence: 99%
“…Sustained rainfall processes are often concomitant by changes in the accompanying meteorological factors such as temperature, humidity, wind speed and direction, which will affect the removal effect to varying degrees [33]. Therefore, in this paper, we conside the effect and intensity of the existing influence factors [34][35][36][37], and balance the availabil ity of their own observational data and the predictability of future trends to establish a se of accompanying influence factors F, including the (i) direct factor (FD) to describe rainfal characteristics, and the (ii) indirect factor (FI) to describe environmental characteristics The factors and impact effects are shown in Table 1.…”
Section: Sustained Rainfall Removal Concomitant Factor Modelingmentioning
confidence: 99%